Switchable Plasmonic Metasurface Utilizing the Electro-Optic Kerr Effect of a Blue Phase Liquid Crystal - Atorf, Bernhard; Friesen, Simon; Rennerich, Roman; Mühlenbernd, Holger; Zentgraf, Thomas; Kitzerow, Heinz-Siegfried (Polymer Science, Series C)

Liquid crystalline dithienothiophene derivatives for organic electronics - Vollbrecht, Joachim; Oechsle, Peter; Stepen, Arne; Hoffmann, Florian; Paradies, Jan; Meyers, Thorsten; Hilleringmann, Ulrich; Schmidtke, Jürgen; Kitzerow, Heinz-Siegfried (Organic Electronics)

Blends of Two Perylene Derivatives: Mesogenic Properties and Application As Emitter Materials in OLEDs - Vollbrecht, Joachim; Stepen, Arne; Nolkemper, Karlo; Keuker-Baumann, Susanne; Kitzerow, Heinz-Siegfried (Polymer Science, Series C)
Keywords: Materials Chemistry; Polymers and Plastics; General Chemistry

Two-dimensional switchable blue phase gratings manufactured by nanosphere lithography - Wahle, M.; Brassat, Katharina; Ebel, J.; Bürger, Julius; Lindner, Jörg; Kitzerow, Heinz-Siegfried (Optics Express 25)
Switchable two dimensional liquid crystal diffraction gratings are promising can- didates in beam steering devices, multiplexers and holographic displays. For these areas of applications a high degree of integration in optical systems is much sought-after. In the context of diffraction gratings this means that the angle of diffraction should be rather high, which typically poses a problem as the fabrication of small grating periods is challenging. In this paper, we propose the use of nanosphere lithography (NSL) for the fabrication of two-dimensionally structured electrodes with a periodicity of a few micrometers. NSL is based on the self-assembly of micro- or nanometer sized spheres into monolayers. It allows for easy substrate structuring on wafer scale. The manufactured electrode is combined with a liquid crystalline polymer-stabilized blue phase, which facilitates sub-millisecond electrical switching of the diffraction efficiency at adiffractionangle of 21.4°.

Ferroelectric Liquid Crystals in Microcapillaries: Observation of Different Electro-optic Switching Mechanisms - Knust, Steffen; Wahle, Markus; Kitzerow, Heinz-Siegfried (The Journal of Physical Chemistry B)
Keywords: Materials Chemistry; Surfaces; Coatings and Films; Physical and Theoretical Chemistry

Electroluminescent and Optoelectronic Properties of OLEDs with Bay-Extended, Distorted Perylene Esters as Emitter Materials - Vollbrecht, Joachim; Blazy, Simon; Dierks, Philipp; Peurifoy, Samuel; Bock, Harald; Kitzerow, Heinz-Siegfried (ChemPhysChem)
Keywords: Physical and Theoretical Chemistry; Atomic and Molecular Physics; and Optics

Two-dimensional switchable blue phase gratings manufactured by nanosphere lithography - Wahle, Markus; Brassat, Katharina; Ebel, Justus; Bürger, Julius; Lindner, Jörg K. N.; Kitzerow, Heinz-Siegfried (Optics Express)
Keywords: Atomic and Molecular Physics; and Optics

Plasmonic nanostructures: spectroscopy and electron microscopy - Kitzerow, Heinz-Siegfried; Lindner, Jörg

Tunable plasmonic structures utilizing liquid crystals - Atorf, B.; Rasouli, H.; Rennerich, R.; Muhlenbernd, H.; Reineke, B. J.; Zentgraf, T.; Kitzerow, Heinz-Siegfried (2017 11th International Congress on Engineered Materials Platforms for Novel Wave Phenomena (Metamaterials))

Liquid crystal medium and liquid crystal display - Wilkes, D.; Wittek, M.; Hoischen, A.; Kitzerow, Heinz-Siegfried; Nordendorf, G.; Schmidtke, J.

Organic Thin-Film Transistors for AMOLED Applications - Meyers, Th.; Vollbrecht, J.; Vidor, F.; Reker, J.; Kitzerow, Heinz-Siegfried; Hilleringmann, Ulrich (IEEE Xplore, MikroSystemTechnik 2017)

Enhanced columnar mesophase range through distortions in arene cores - Vollbrecht, Joachim; Wiebeler, Christian; Schumacher, Stefan; Bock, Harald; Kitzerow, Heinz-Siegfried (Molecular Crystals and Liquid Crystals)

Liquid crystals and precious metal: from nanoparticle dispersions to functional plasmonic nanostructures - Atorf, Bernhard; Funck, Timon; Hegmann, Torsten; Kempter, Susanne; Liedl, Tim; Martens, Kevin; Mühlenbernd, Holger; Zentgraf, Thomas; Zhang, Bingru; Kitzerow, Heinz-Siegfried; Urbanski, Martin (Liquid Crystals)
Keywords: Condensed Matter Physics; General Materials Science; General Chemistry

Near infrared Kerr effect and description of field-induced phase transitions in polymer-stabilized blue phase liquid crystals - Atorf, B.; Rasouli, H.; Nordendorf, G.; Wilkes, D.; Kitzerow, Heinz-Siegfried (Applied Physics Letters)
Keywords: Physics and Astronomy (miscellaneous)

The International Liquid Crystal Society 1990–2015 - Dunmur, David; Kitzerow, Heinz-Siegfried (Liquid Crystals Today)
Keywords: Materials Chemistry; Inorganic Chemistry; Condensed Matter Physics

Temperature-insensitive electro-optic response of polymer-stabilized blue phases - Nordendorf, Gaby; Schmidtke, Jürgen; Wilkes, David; Kitzerow, Heinz-Siegfried (Journal of Materials Chemistry C)
Polymer-stabilized blue phase liquid crystal in-plane switching cell.
Keywords: Materials Chemistry; General Chemistry

Asymmetric band gap shift in electrically addressed blue phase photonic crystal fibers - Wahle, M.; Ebel, J.; Wilkes, D.; Kitzerow, Heinz-Siegfried (Optics Express)
Keywords: Atomic and Molecular Physics; and Optics

Asymmetric band gap shift in electrically addressed blue phase photonic crystal fibers - Wahle, M.; Ebel, J.; Wilkes, D.; Kitzerow, Heinz-Siegfried (Optics Express)
Keywords: Atomic and Molecular Physics; and Optics

Metallic and semiconducting nanoparticles in LCs - Sharma, Anshul; Urbanski, Martin; Mori, Taizo; Kitzerow, Heinz-Siegfried; Hegmann, Torsten (Series in Soft Condensed Matter)

Influence of Proton and Salt Concentration on the Chromonic Liquid Crystal Phase Diagram of Disodium Cromoglycate Solutions: Prospects and Limitations of a Host for DNA Nanostructures - Zhang, Bingru; Kitzerow, Heinz-Siegfried (The Journal of Physical Chemistry B)
Keywords: Materials Chemistry; Surfaces; Coatings and Films; Physical and Theoretical Chemistry